Titania supported on silica as an efficient catalyst for deep oxidative desulfurization of a model fuel with exceptionally diluted H2O2. Issue 1 (25th January 2018) - Piscopo, C. G.; Tochtermann, J.; Schwarzer, M.; Boskovic, D.; Maggi, R.; Maestri, G.; Loebbecke, S.
Abstract : The continuous ODS of a model fuel, catalyzed by titanium nanocrystals dispersed onto silica, was performed with <1% aqueous H2 O2 . Abstract : Deep oxidative desulfurization has been carried out, achieving the production of a model fuel with minimal sulphur content (0–15 ppm). This desulfurization process has been developed in continuous flow, using a titanium supported heterogeneous catalyst and exceptionally low hydrogen peroxide concentration (0.77% w/w).